Relationship of recovered hepatitis B infection with appearance of toxic propylthiouracil hepatitis - Lejla Čalkić; Lejla Bajramović-Omeragić (Medicinski glasnik, 2017)
Aim: To investigate the relationship between recovered hepatitis B infection with appearance of toxic propylthiouracil (PTU) hepatitis and point out the growing importance of the use of drugs in the development of hepatitis. Methods: A case of a 45-year-old female patient with suspicion of acute viral hepatitis who had polypragmasy of drugs in the last ten years, due to the polymorphism of symptoms/illnesses (diabetes mellitus, depression, hypertension, hypothyroidism) was presented. Results: A female patient had hyperthyroidism after resolved viral hepatitis B with HBsAg seroconversion (HBsAg negative, antiHBs positive). PTU had the greatest potential for hepatotoxicity of all administered drugs. After corticosteroid therapy there was a significant improvement in liver function tests. In the course of the disease there was no change of hepatitis markers and exacerbations of hepatitis B. Conclusion: Clinical practice should comprehensively monitor the effects of the intricate and tight connection between drugs, liver and endocrine system in order to better resolve all manifestations, complications and worsening of one or another organic system.
Keywords: drugs; hepatotoxicity; hyperthyroidism; HBsAg seroconversion